#### Answer

graph of $y-3=-2x$:

#### Work Step by Step

In the form $y=mx+b,$ the given equation, $
y-3=-2x
,$ is equivalent to
\begin{align*}
y-3+3&=-2x+3
\\
y&=-2x+3
.\end{align*}
Using $y=mx+b$ or the Slope-Intercept Form of linear equations, where $b$ is the $y$-intercept and $m$ is the slope, the equation above has the following characteristics:
\begin{align*}
\text{$y$-intercept: }&
3
\\
\text{Slope: }&
-2\text{ or }\dfrac{-2}{1}
.\end{align*}
To graph the slope-intercept equation above, start at the $y$-intercept. This corresponds to the point $
(0,3)
$.
Using the notion of the slope as $\dfrac{rise}{run},$ then $rise=
-2
$ and $run=
1
.$
From the $y$-intercept, go $\text{
down
}$ by $rise=
-2
$ units and then go to the right by $run=
1
$ units.
This results to the point $
(1,1)
.$
Connecting this point and the $y$-intercept gives the graph of the given equation.